2020
DOI: 10.15219/em86.1482
|View full text |Cite
|
Sign up to set email alerts
|

Learning analytics in synchronous online education: Making video conferencing more data-driven and interactivity-focused

Abstract: COVID-19 has been a turning point for online learning across the world, but the remarkable story has been the meteoric growth of synchronous or “live” online education. As instructors around the world have turned to video conferencing platforms to teach, a lot of instructor feedback has recently emerged on a variety of topics. One of the key emerging issues for instructors and institutions has been extracting and consolidating data on student engagement and learning outcomes. This paper attempts to identify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rugube, T. et al reviewed and outlooked the network analysis methods of online learning interactions, and concluded that discovering the interaction evolution laws and mechanisms based on the dynamic network analysis perspective has become the focus of research [11]. Vashisht, V. and Gautam , P. modeled the connective structure of learner interactions and cognitive processes by visually presenting and interpreting complex cognitive structures, tracking and characterizing multidimensional associations between participants' multidimensional interactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rugube, T. et al reviewed and outlooked the network analysis methods of online learning interactions, and concluded that discovering the interaction evolution laws and mechanisms based on the dynamic network analysis perspective has become the focus of research [11]. Vashisht, V. and Gautam , P. modeled the connective structure of learner interactions and cognitive processes by visually presenting and interpreting complex cognitive structures, tracking and characterizing multidimensional associations between participants' multidimensional interactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Their use can be poor without elements such as collaborations, tutorials, resources, and well-articulated content. Tracking the level of student engagement in online lessons is also a difficult task [6]. In addition, during the COVID-19 pandemic, students may express a preference for face-to-face education [7] and may become averse to online learning.…”
Section: Introductionmentioning
confidence: 99%